INFLUENCE OF GLYCERYL POLYETHYLENE GLYCOL RICINOLEATE (GPEGR) ON PRODUCTION PERFORMANCE OF BROILER CHICKEN - N. Dinesh Kumar; M. Ramachandran; K. Ayyappan; C. Mehala (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted to evaluate the effect of glyceryl polyethylene glycol ricinoleate (GPEGR) supplementation on the production performance in broiler chicken. A total of two hundred day-old broiler chicks were randomly assigned to five dietary treatments  containing forty birds in each  group with five replicates in each treatment group and thus constituting  eight birds per replicate . The control group (C) received basal diet, T1 group received the basal diet and GPEGR, while the T2, T3, and T4 groups received GPEGR-supplemented diets with graded reductions in energy density by 20, 40, and 60 kcal/kg, respectively. All the birds were maintained under uniform and standard managemental conditions with  access to ad-libitum feed and water. The study found that the final body weight and average daily gain (ADG) in the T1 group (1804.99 g and 50.21 g, respectively) were significantly (P0.05) differences among the groups. It can be concluded that the feeding of GPEGR supplemented diet containing 3000 Kcal per kg enhanced the growth rate  in broiler chicken